2022
DOI: 10.55587/jla.v2i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance, Likuiditas, Tax Avoidance: Ukuran Perusahaan Sebagai Variabel Moderasi

Abstract: Tujuan: Penelitian ini bertujuan untuk membuktikan pengaruh corporate governance dan likuiditas terhadap tax avoidance dengan ukuran perusahaan sebagai variabel moderasi. Elemen corporate governance yang digunakan adalah komisaris independen dan komite audit. Metode: Sampel dipilih dengan menggunakan teknik purposive sampling dengan hasil 22 perusahaan properti dan real estate yang terdaftar di Bursa Efek Indonesia dari tahun 2016 hingga 2019. Teknik analisis data dengan analisis linear berganda dan Moderated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
1
1
1
Order By: Relevance
“…The results of this study are the same as those of research conducted by Cahyadi et al (2020) and Asih (2021), which show that firm size can moderate the influence between liquidity and tax aggressiveness. However, this research differs from those conducted by Kinasih (2021) and Hanifah (2021), which state that firm size cannot moderate the effect of liquidity on tax aggressiveness. The company's size is associated with the amount of liabilities owned by the company.…”
Section: The Effect Of Liquidity On Tax Aggressiveness Through Firm Sizecontrasting
confidence: 77%
“…The results of this study are the same as those of research conducted by Cahyadi et al (2020) and Asih (2021), which show that firm size can moderate the influence between liquidity and tax aggressiveness. However, this research differs from those conducted by Kinasih (2021) and Hanifah (2021), which state that firm size cannot moderate the effect of liquidity on tax aggressiveness. The company's size is associated with the amount of liabilities owned by the company.…”
Section: The Effect Of Liquidity On Tax Aggressiveness Through Firm Sizecontrasting
confidence: 77%
“…This is supported by research by JayantoPurba & Dwi, (2020); Herlinda & Rahmawati, (2021);Kulsum, (2020) found that liquidity has a positive effect on tax aggressiveness, while research Herlinda & Rahmawati, (2021) states that liquidity has a negative effect on tax aggressiveness and research by Yogiswari & Ramantha, (2017) states that liquidity has no effect on tax aggressiveness. Based on the results of this research, the researcher formulated a hypothesis: H 2 : Liquidity has a positive effect on tax aggressiveness Good Corporate Governance can weaken the influence of profitability on tax aggressiveness One element of good corporate governance is the existence of an independent board of commissioners Supervision and control provided by independent commissioners can reduce the possibility of managers acting undisciplined and aggressively in managing company taxes (Nur Hanifah, 2022). According to research by Wardani et al, (2022) the presence of independent commissioners is negatively related to the level of aggressiveness in tax strategies.…”
Section: The Influence Of Liquidity On Tax Aggressivenessmentioning
confidence: 99%
“…Besar laba maka pajak tinggi, perusahaan berusaha untuk mengurangi pajak dengan bertindak agresif terhadap pajak. Penelitian mengenai pengaruh firm size terhadap hubungan likuiditas dan agresivitas pajak diantaranya penelitian dari (Nur Hanifah, 2022) dan (Cahyadi et al, 2020) menyatakan bahwa "firm size mampu memoderasi pengaruh likuiditas terhadap agresivitas pajak" .…”
Section: Pengaruh Firm Size Terhadap Hubungan Antara Likuiditas Dan A...unclassified